Zarzut epifenomenalizmu jako zarzut zewnętrzny względem monizmu anomalnego - Paprzycka, Katarzyna (Filozofia Nauki, 2011)
The paper is a critical reaction to M. Grygianiec’s discussion of the status of the epiphenomenalism objection to anomalous monism. Grygianiec argues that the objection does not arise for Davidson if one takes his nominalism seriously. I show that Grygianiec construes the epiphenomenalism charge as an internal one. I argue that it can be viewed as an external objection to anomalous monism, moreover one that is justified, adequate and charitable. I distinguish two interpretations of the objection and show that an appeal to charity can explain why an apparently inadequate form the objection is often preferred.